Dinamika Interaksi Antara Karyawan Tetap dan Karyawan Kontrak di Lingkungan Hotel - Ida Ayu Sulastri; I Gusti Nyoman Wiantara (Journal Research of Management, 2024)
The hospitality industry operates within a complex work dynamic, requiring collaboration between permanent and contract employees. This study aims to understand the interaction between these two groups in hotels located in Badung, Bali, focusing on collaboration, communication, task allocation, perceptions of fairness, and the impact of employment status differences on team productivity. A descriptive qualitative design was employed, using simple random sampling to select 34 respondents from various hotels in Badung. Data were collected through closed questionnaires and open-ended responses. The findings reveal that working relationships between permanent and contract employees are generally positive and professional, supported by effective communication and strong coordination. However, challenges persist, including perceptions of unfairness in benefits, career development opportunities, and unequal compensation. Good communication helps maintain team harmony, although contract employees may face difficulties expressing themselves in formal settings. Minor conflicts are usually resolved through communication and mutual understanding. The study recommends developing inclusive and fair policies, implementing joint training to strengthen team synergy, and creating participatory opportunities for contract employees in decision-making processes. Effective management can foster a harmonious work environment, enhance employee satisfaction, and support the sustainable operation of hotels.